Asuhan Keperawatan Pada Nn. R dan Nn.I Yang Mengalami Masalah Gangguan Sensori Persepsi Halusinasi Pendengaran Pada Skizofrenia Paranoid di Ruang Cempaka Rumah Sakit Jiwa Dr. Soeharto Heerdjan Jakarta - Fitriningsih, Falia Al; Prihatini, Fitria; Vestabilivy, Evi (Jurnal Persada Husada Indonesia, 2024)
Paranoid schizophrenia is a neurological disease with the main symptoms of extreme spectacles accompanied by delusions of greed or grandiosity. Hallucinations are one of the sensory perception disorders, where there is a five-sensory experience without any sensory stimulation or a false sense perception. Auditory hallucinations are hearing voices or complete conversations between two or more people in which the patient is told to do something that is sometimes dangerous. Auditory hallucinations are influenced by 2 factors, namely predisposition and precipitation. The research used is a qualitative descriptive research method with intervention. From the results of the study, it was found that Ms.R's predisposing factors were socio-cultural and environmental, while Ms.I's were psychological, socio-cultural, and environmental. The precipitating factors for both patients are biological, psychological, and socio-cultural. There were 7 similar deaths found in Ms. In the planning, implementation strategies were carried out for sensory perception disorders, auditory hallucinations, and self-care deficits in both patients. Both patients can carry out strategies for controlling hallucinations, rebuking them by drinking, controlling hallucinations by taking medication and implementing strategies for self-care deficits. After breastfeeding treatment, patients can control hallucinations by shouting, taking the medication regularly, having conversations, and carrying out activities as well as maintaining personal hygiene and grooming. Advice to nurses to continue to carry out therapeutic communication with patients.